2021
DOI: 10.1039/d1sm00839k
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the antimicrobial activity of peptide hydrogel systems: current and future perspectives

Abstract: The use of hydrogels has garnered significant interest as biomaterial and drug delivery platforms for anti-infective applications. For decades antimicrobial peptides have been heralded as a much needed new class...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 160 publications
0
17
0
Order By: Relevance
“…The key factors for the self-assembly of peptides are chemical complementarity and structural compatibility among molecules through noncovalent bond interactions. By adjusting the type, position of hydrophilic and hydrophobic amino acids, and secondary structure, AMPs can be self-assembled to form peptide aggregates with different morphologies. Goel et al reported a short self-assembled amphiphilic mixed α/β-pentapeptide (H-Lys-βAla-βAla-Lys-βAla-OEt), which can self-assemble into nanoscale vesicles, showing excellent stability and enhanced antimicrobial activity compared to peptides containing only α-amino acids . In a study of the interaction between the self-assembled nanopeptide PTP-7b and cells, Chen and coworkers noted that the self-assembly ability of the peptide was as important to the antibacterial effect as the number of charges and secondary structure .…”
Section: Introductionmentioning
confidence: 99%
“…The key factors for the self-assembly of peptides are chemical complementarity and structural compatibility among molecules through noncovalent bond interactions. By adjusting the type, position of hydrophilic and hydrophobic amino acids, and secondary structure, AMPs can be self-assembled to form peptide aggregates with different morphologies. Goel et al reported a short self-assembled amphiphilic mixed α/β-pentapeptide (H-Lys-βAla-βAla-Lys-βAla-OEt), which can self-assemble into nanoscale vesicles, showing excellent stability and enhanced antimicrobial activity compared to peptides containing only α-amino acids . In a study of the interaction between the self-assembled nanopeptide PTP-7b and cells, Chen and coworkers noted that the self-assembly ability of the peptide was as important to the antibacterial effect as the number of charges and secondary structure .…”
Section: Introductionmentioning
confidence: 99%
“…Polypeptide hydrogels have optimized mechanical strength and can resist shear stress to the wound and selectively inhibit specific bacteria when incorporated with antibacterials to reduce drug resistance. In the past decade, peptide hydrogels with antibacterial effects have been effective in the treatment of all stages of infection, mainly for the treatment of S. aureus , MRSA , S. epidermidis , E. coli , P. aeruginosa and K. pneumoniae , and future research will be focused on designing species-specific hydrogels [ 109 ]. Scientists found that when multi-domain peptide hydrogels have different charges, they can produce various regulatory effects on the host immune response.…”
Section: Reviewmentioning
confidence: 99%
“…One of the simplest and most widely recognized motifs in peptide self-assembly is the diphenylalanine (or analogously, polyphenylalanine) motif, which is the most-minimalistic motif in driving self-assembly by π-π stacking interactions ( Fig. 2 ) [81] , [82] . It has also been demonstrated that FF (diphenylalanine) assembles into nanostructures which significantly inhibited the growth of E. coli , besides having biocidal properties against Listeria monocytogenes and Staphylococcus epidermidis [83] .…”
Section: Role Of Self-assembly In Amp Activitymentioning
confidence: 99%